2022
DOI: 10.1088/1742-6596/2315/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of silicic acid saturation and gel formation during ISG leaching: 180 days duration reaction at 90 °C

Abstract: Currently, borosilicate glasses are utilised to immobilise highly radioactive waste. They are durable materials; however, they corrode in aqueous solutions, resulting in silica-rich alteration layers. This study employed the nuclear waste leaching tests (MCC-1, MCC-3) on International Simple Glass (ISG) samples. The corrosion rate in pure water and saturated water with respect to ISG corrosion products was investigated at an initial pH of 6.3 and a reaction temperature of 90 °C. For 3, 7, 14, 28, 90, and 180 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…A large number of studies have shown that an alteration layer (AL) is often created on a glass surface in the long-term corrosion process, and the formation of the alteration layer will slow down the further corrosion process [21,22]. The microstructure of the alteration layer is extremely complex and very different from the original glass, such as "hydrated glass" or "mutual diffusion layer", amorphous layer rich in silica, precipitate layer formed by secondary minerals and so on [23][24][25][26]. The complex microstructure of the alteration layer has a great influence on the mechanical properties of the glass surface [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that an alteration layer (AL) is often created on a glass surface in the long-term corrosion process, and the formation of the alteration layer will slow down the further corrosion process [21,22]. The microstructure of the alteration layer is extremely complex and very different from the original glass, such as "hydrated glass" or "mutual diffusion layer", amorphous layer rich in silica, precipitate layer formed by secondary minerals and so on [23][24][25][26]. The complex microstructure of the alteration layer has a great influence on the mechanical properties of the glass surface [27,28].…”
Section: Introductionmentioning
confidence: 99%